Ações dos enfermeiros em Saúde Mental na Estratégia Saúde da Família. - Gonçalves, Rejane Maria Dias de Abreu (2009)
Introduction: The nursing field is expanding nowadays and it has an outstanding meaning. It is in charge of taking care and promoting new insertion in social life of each person, yet respecting their subjectivity. The insertion of nurses´actions in Mental Health is necessary in the of Family Health Strategy (FHS), as well as searching the understanding of the complexity of Mental Health in building more efficient and qualified practices. Objectives: Identifying the social and demographic profile of the nurses inserted in FHS, and also describing the actions of Mental Health performed by these nurses in the city of Uberaba/MG-Brazil. Methodology: Crosssectional study carried out with 45 nurses inserted in FHS in Uberaba/MG, from February to May, 2009. The data were collected though an instrument containing social demographic and economic variables, improving and skill in Mental Health, and also through another instrument with variables related to the actions of the nurse in Mental Health in FHS, which was divided into four distintive stages. They are: Actions in the first contact; actions carried out for the promotion and prevention in Mental Health; continuous actions in Mental Health and actions to sort out the problems in Mental Health in FHS. The analysis was done by means of distribution of frequencies. Outcome: Within the 45 nurses, 93,3% are female; (57,8%) are single; (60,9%) are aged between 20 to 29, (73,9%) graduated in the last five years, (60,9%) has had working experience of one to three years in FHS; (77,8%) are specialists; (60%) claimed not having specific graduation in Mental Health and (68%) do not feel prepared to deal with Mental Health in FHS. The acceptance (100%), hearing (84,4%), orientation (62,2%), raising of basic needs of the users (60%) and the attention paid to verbal communication (60%) were actions listed in the first stage. In the second stage, acceptance (84,4%), orientation (77,8%), education in health (68,9%), family support (60%) and physical exercises (53,3%) are highlighted. In the third stage, home visits are emphasized (80%), as well as acceptance (77,8%), family support (68,9%), recommendation (66,7%) and medication follow-up (53,3%). The fourth stage is characterized by self care (82,2%), directions (64,4%), the attempt to decrease hopelessness in users (57,8%), the analysis of users´capacity in dealing with the problems (53,3%), and the articulation of therapeutic actions with specialized services of Mental Health (51,1%). Lack of protocol in Mental Health (75,6%), lack of capability (57,8%), inadequate education (53,3%) and priority of FHS concerning other programmes in health care (51,1%) are shown as factors which may cause difficulties in the actions of Mental Health in FHS. Discussion: Despite the difficulty and lack of preparation of the nurses dealing with Mental Health in SFH, and for not having specific education in this field, the results of this study show that the nurses performed actions in Mental Health in all the established stages in this study. However, it was observed throughout this research that some actions were not highlighted as meaningful by the nurses, such as non verbal communication, therapeutic groups and family genogram.